Indústrias criativas, criatividade e inovação na perspectiva da Geração Z. - Silva Neto, Hildo Pereira da (2020)
The generational study stands out as an important factor for society to understand the behavior of certain portions of the population, as well as the interaction between different generations. The objective of this research was to understand the understanding of Generation Z of Recife, formed by university students, about Creative Industries, Creativity and Innovation. The questionnaire was applied to 100 young people from higher education institutions and different areas of knowledge in the capital of Pernambuco. To obtain the data, it was decided to use a questionnaire via the internet. The research has a quanti-quali character, as it brought quantitative and qualitative aspects. The results showed that the term Creative Industries is unknown to a large part of Generation Z, that 79% consider themselves creative and that the interviewees were divided when asked if they are receiving innovative training. The data show that despite consuming Creative Industries, young people are not familiar with the term and that creativity and innovation are aspects valued by the interviewees.